PENGARUH MEDIA BOOKLET DIGITAL 1000 HARI PERTAMA KEHIDUPAN TERHADAP PENGETAHUAN REMAJA PUTRI SEBAGAI UPAYA PENCEGAHAN STUNTING DI SMA KABUPATEN BANDUNG (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: Ciparay District is one of the 8 priority district to handling stunting. Stunting can be prevented by first 1000 days of life which is a crucial period for toddlers. Young woman become important targets to prevent stunting by early providing health education about first 1000 days of life by using digital booklet. Purpose: Knowing the effect of digital booklet first 1000 days of life on young woman's knowledge. Methods: The research used quasi-experimental design with one group pretest-posttest without control to a sample of 83 students in population 497 which taken by stratified sampling. Result: The average score of young woman’s knowledge before given a digital booklet is 69,87. The average score of young woman’s knowledge after given a digital booklet is 90,43. The percentage of increased knowledge is 20,56%. The p value on both before and after young woman’s are given a gidital booklet by using the Wilcoxon test is (p=0,000). Conclusion: There was a significant increase in knowledge after been a given health education in digital booklet of 1000 first days of life to young woman in SMAN 1 Ciparay Bandung District.